PENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI METODE DRILL DAN DISKUSI KELOMPOK PADA SISWA KELAS VI SD - Juniati, Erlyn (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2017)
One of the main problems of todays Mathematics Lesson is the lack of understanding and motivation of teachers in schools, so that children are less active in the learning process. This phenomenon occurs in SD N I Badran. Based on the results of formative tests of class VI semester 2 subjects mathematics of the material change the common fractions into decimal fractions and percent or otherwise low, this is validated by the analysis of the average grade 58, 33. Of the 30 students who achieve the value of learning mastery only 11 students, The rest is still far below KKM (â¤70). Students do not yet understand in changing the usual fractions to decimal fractions and percent or vice versa. This type of research is Classroom Action Research. The subjects studied were the 6th graders of SD Negeri I Badran, Kranggan Sub-district, Temanggung Semester 2 of the 2015/2016 Lesson Study. This study was conducted in 2 cycles, each cycle consisting of 3 meetings, and each cycle consisted of planning, action, observation and reflection. From the result of research by using Drill method and group work, there is an increase of student learning result. In learning mathematics subject matter converts the usual fractions into decimal fractions and percent and vice versa. Prior to the improvement of the number of 30 students who thoroughly studied with KKM 70 only 11 students, with an average score of 58, 33 with mastery learning 36, 66. Improvement of learning Cycle 2 first meetings average grade 83.33 complete 25 percentage of mastery 83.33%. The researcher concludes that the result of the study of the sixth graders of SD Negeri 1 Badran of Kranggan Sub-district of Temanggung Regency on the subject changed the common denominations to decimal and percent and vice versa through Drill method and Group Discussion of learning result increased.